Osmotic stress-dependent serine phosphorylation of the histidine kinase homologue DokA - Oehme, Felix (BioMed Central, 2001)
BACKGROUND: Two-component systems consisting of histidine kinases and their corresponding receivers are widespread in bacterial signal transduction. In the past few years, genes coding for homologues of two-component systems were also discovered in eukaryotic organisms. DokA, a homologue of bacterial histidine kinases, is an element of the osmoregulatory pathway in the amoeba Dictyostelium. The work described here addresses the question whether DokA is phosphorylated in vivo in response to osmotic stress. RESULTS: We have endogenously overexpressed individual domains of DokA to investigate post-translational modification of the protein in response to osmotic shock in vivo. Dictyostelium cells were labeled with [(32)P]-orthophosphate, exposed to osmotic stress and DokA fragments were subsequently isolated by immunoprecipitation. Thus, a stress-dependent phosphorylation could be demonstrated, with the site of phosphorylation being located in the kinase domain. We demonstrate biochemically that the phosphorylated amino acid is serine, and by mutational analysis that the phosphorylation reaction is not due to an autophosphorylation of DokA. Furthermore, mutation of the conserved histidine did not affect the osmostress-dependent phosphorylation reaction. CONCLUSIONS: A stimulus-dependent serine phosphorylation of a eukaryotic histidine kinase homologue was demonstrated for the first time in vivo. That implies that DokA, although showing typical structural features of a bacterial two-component system, might be part of a eukaryotic signal transduction pathway that involves serine/threonine kinases.